Qualidade de vida dos idosos hipertensos e diabéticos atendidos no ambulatório de um hospital de ensino do interior de São Paulo - Esteves, Marlene (2011)
The world population has been aging. This requires special attention from health care services to provide the complexity in morbimortality profile of the elderly. High Blood Pressure (HBP) and Diabetes Mellitus (DM) are chronic diseases and risk factors for cardiovascular diseases, which are the major cause of morbidity and mortality of Brazilian population. This study aimed at evaluating the quality of life regarding the health (QLRH)) of elderly hypertensive and / or diabetic outpatients attended in a school hospital in the interior of Sao Paulo state. This is a descriptive, cross-sectional study performed in the outpatient service of the Geriatrics Medical Clinics of São José do Rio Preto, with 62 elderly patients with HBP and / or DM treated at this clinics during the period from November 2009 to February 2010. To collect data the WHOQOL-OLD questionnaire and the Statistical Package for Social Sciences (SPSS) software were used. They were analyzed by means of descriptive statistics through non-parametric tests like Mann-Whitney and Kruskal-Wallis test and Pearson´s correlation with coefficient test ; the level of significance was p <0.05. Elderly patients with HBP and / or DM had no statistical difference in all facets of the questionnaire QLRH WHOQOL - OLD, but had a greater impact on the facet autonomy and higher scores in these domains: the sensory functioning, past present and future activities, social participation, death and dying and intimacy. The results of this study can provid the care of needs and peculiarities of these patients.